"Teach to adapt or adapt to teach": qualitative study on the new "special-post teachers" in China's rural schools. Issue 12 (15th October 2021) - Li, Jian; Xue, Eryong
Abstract: The number of new "Special-post teachers" has decreased considerably, especially at China's rural schools in recent years. This study applies the semi-structured interview data of new "Special-post teachers" in China's rural schools to explore their perceptions on the rural new teachers' problems and challenges at nine developing rural provinces in China. It finds that the new rural teachers were confronted with severe challenges and difficulties for their professional adaptability in rural areas, such as the interpersonal relationship, heavy workload and dissatisfied salary, and unqualified teaching capacities. Those interviewed new "Special-post teachers" also learned lots from those challenges in reality, such as the diversified personality characteristics, professional beliefs and career motivation. It also suggested that, Chinese government should offer sufficient and diversified educational policies to stimulate rural teacher development, especially for new "Special-post Teachers" at rural areas. Chinese central government plays a significant role to guarantee the sustainable funding support for the development of new "Special-post teachers". In addition, the principals in rural schools should pay close attention to new Special-post Teachers' personability characteristics, hobbies and needs to create a supportive teaching environment for them to move toward successful rural teacher development.